Our Only Teachers Are Those Who Tell Us: ‘Do Together with Me - Camargo, Juan (2021)
“Our Only Teachers Are Those Who Tell Us: ‘Do Together with Me’”: Approaches to an Idea of Education in Difference and Repetition by Gilles Deleuze”. In the most recent bibliography about Deleuze’s philosophical work, there is no research that studies the relationship between an idea of education and his book Difference and Repetition. This article explores and interprets, based on the ontology of Deleuze, an idea of education. The understanding of the concepts of “difference and repetition” and “the dramatization method”, allows me to think how to inscribe them in the educational field, which are their consequences and what is their scope. These ideas invite us to return to the themes of intellectual emancipation and equality, based on Jacotot’s and Renciere’s works.